2004
DOI: 10.1039/b315483a
|View full text |Cite
|
Sign up to set email alerts
|

Solvent templated synthesis of metal–organic frameworks: structural characterisation and properties of the 3D network isomers {[Mn(dcbp)]·½DMF}nand {[Mn(dcbp)]·2H2O}n

Abstract: The identity of the metal-organic framework formed by Mn(ii) and 4,4[prime or minute]-dicarboxy-2,2[prime or minute]-bipyridine (H(2)dcbp) depends upon the predominant solvent employed in the synthesis and yields the robust network isomers [[Mn(dcbp)][middle dot]1/2DMF](n), and [[Mn(dcbp)][middle dot]2H(2)O](n), which possess vastly different physical properties: irretrievably binds DMF, whereas reversibly binds water whilst retaining crystallinity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(39 citation statements)
references
References 17 publications
0
39
0
Order By: Relevance
“…However, analysis of FTIR spectra ( Fig. 1) for sDMF 220 showed the presence of a spectral peak at 1660 cm À1 attributed to m(C@O) in DMF molecules that remain trapped in the material; an observation made in other MOFs when using DMF in place of H 2 O as the synthesis solvent [16]. Several washing steps with methanol were repeated in an attempt to remove the DMF molecules from the framework; however, it was found that these repeated washing steps did not remove the trapped species, suggesting these molecules are coordinated to the metal center or to the benzene ring of the ligand.…”
Section: Resultsmentioning
confidence: 94%
“…However, analysis of FTIR spectra ( Fig. 1) for sDMF 220 showed the presence of a spectral peak at 1660 cm À1 attributed to m(C@O) in DMF molecules that remain trapped in the material; an observation made in other MOFs when using DMF in place of H 2 O as the synthesis solvent [16]. Several washing steps with methanol were repeated in an attempt to remove the DMF molecules from the framework; however, it was found that these repeated washing steps did not remove the trapped species, suggesting these molecules are coordinated to the metal center or to the benzene ring of the ligand.…”
Section: Resultsmentioning
confidence: 94%
“…Currently, the most commonly used N-heterocyclic carboxylic ligands mainly include pyridinecarboxylic acids [3-5], terpyridinecarboxylic acids [6], imidazolecarboxylic acids [7,8], triazolecarboxylic acids [9]. Although 2,2′-bipyridyl-4,4′-dicarboxylic acid as a polydentate ligand has been extensively exploited [10][11][12][13][14][15][16][17], investigations on 2,2′-bipyridyl-5,5′-dicarboxylic acid (H 2 bpdc) as a multifunctional ligand remain largely unexplored [18][19][20][21][22][23][24][25]. Obviously, most of reported metal complexes are the noble metal derivatives, which provides us an excellent opportunity for exploring the reaction of the first-row transition-metal/lanthanide cations with H 2 bpdc based on the following considerations: (a) the flexible multifunctional H 2 bpdc with N and O donor atoms can provide the large possibility for constructing novel structures; (b) H 2 bpdc can be deprotonated to generate Hbpdc − and bpdc 2− , allowing various acidity-dependent coordination modes; and (c) first-row transition-metal cations have a strong affinity to both N-and O-donors while lanthanide cations prefer O-donors to N-donors according to the hard-soft acid base rule.…”
mentioning
confidence: 99%
“…Multi-dentate ligands were used as building blocks to build supramolecular frameworks, and 2,2'-bipyridine -4,4'-dicarboxylic acid (bpdc) is apotential bridging ligand in various coordination modes as aresult of its multifunctional groups. The synthesis, crystal structure and properties on the coordination compounds constructed by bpdc and transition and rare earth metal were investigated [1][2][3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%